Use Plain Language and Unlock Efficiency in Automatic Translation to Libras by Avatars - Silva, André Luiz da Cunha; Ferreira, Simone Bacelar Leal; de Sá, Tatiane Militão; Cappelli, Cláudia (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
As communication is a fundamental human right, fostering social, emotional, and cognitive development, this paper explores the importance of high-quality automatic translation from written Portuguese to Brazilian Sign Language (Libras) in avatar-based communication as an accessibility resource, particularly for deaf pre-linguistic individuals. We present evidence demonstrating the effectiveness of plain language combined with keywords replacement in improving translation quality for this specific audience. A study on improving the efficiency of automatic translation through avatars has been conducted, and the findings have established the benefits of using Plain Language in enhancing the accuracy and speed of automated translation. The study revealed that the use of avatars combined with Plain Language can significantly improve the quality of automated translations. Applying Plain Language before translation by the avatars provided a more nuanced understanding of the context and meaning of the text, reducing the likelihood of errors and mistranslations. Plain Language simplified the translation process, enabling the algorithms to generate translations faster and more accurately. The research was an applied qualitative and exploratory study that involved a bibliographic survey and support from expert interpreters. The study was experimental and conducted through sequential chronological cuts. During the study, prescriptive and semantic analyses were applied to the data. The findings of this research have implications for the field and can help further understanding of the subject matter. The study’s results have significant implications for developing automated translation systems, as they suggest that integrating avatars and plain language could lead to more efficient and reliable translations in various domains. Enhanced translation fosters intercultural communication, message accessibility, and effective human-computer interaction.